1991
DOI: 10.1111/j.1365-2958.1991.tb01876.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptide transport and chemotaxis in Escherichia coli and Salmonella typhimurium: characterization of the dipeptide permease (Dpp) and the dipeptide‐binding protein

Abstract: The dipeptide permease (Dpp) is one of three genetically distinct peptide-transport systems in enteric bacteria. Dpp also plays a role in chemotaxis towards peptides. We have devised three selections for dpp mutations based on resistance to toxic peptides (bacilysin, valine-containing peptides, and bialaphos). All dpp mutations mapped to a single chromosomal locus between 77 and 78 min in Salmonella typhimurium and at 79.2 min in Escherichia coli. Expression of dpp was constitutive in both species but the abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
123
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(129 citation statements)
references
References 61 publications
5
123
1
Order By: Relevance
“…In strains unable to transport dipeptides, but containing wild-type levels of the dipeptide binding protein (DppA), the chemotaxic response towards peptides is comparable to that in the wild type. This is consistent with the notion that only the dipeptide binding protein of Dpp is involved in chemotaxis [1]. Later research showed that at least five different receptors (methyl-accepting chemotaxis proteins (MCPs)) are present in the cytoplasmic membrane of enteric bacteria to recognize attractants.…”
Section: Chemotaxissupporting
confidence: 81%
“…In strains unable to transport dipeptides, but containing wild-type levels of the dipeptide binding protein (DppA), the chemotaxic response towards peptides is comparable to that in the wild type. This is consistent with the notion that only the dipeptide binding protein of Dpp is involved in chemotaxis [1]. Later research showed that at least five different receptors (methyl-accepting chemotaxis proteins (MCPs)) are present in the cytoplasmic membrane of enteric bacteria to recognize attractants.…”
Section: Chemotaxissupporting
confidence: 81%
“…The dpp operon has been shown to be maximally expressed in the stationary phase of growth, with expression driven from the promoter region upstream of the first gene, dppA (Abouhamad & Manson, 1994). In Salmonella typhimurium and Escherichia coli, dppA has been shown to play a role in chemotaxis (Abouhamad et al, 1991). The role of the dpp transport machinery in utilizing haem iron has also been shown in E. coli.…”
Section: Introductionmentioning
confidence: 96%
“…DBP is a 507-residue periplasmic protein involved in chemotaxis toward, and transport of, many dipeptides and some tripeptides (Manson et al, 1986;Abouhamad et al, 1991;Olson et al, 1991). This protein has also been shown to be related to periplasmic receptors for oligopeptides (Guyer et al, 1985;Tame et al, 1994) and nickel (Navarro et al, 1993).…”
mentioning
confidence: 99%